Spatial Mental Transformation Skills Discriminate Fitness to Drive in Young and Old Adults - Tinella, Luigi; Lopez, Antonella; Caffò, Alessandro Oronzo; Grattagliano, Ignazio; Bosco, Andrea (Frontiers in Psychology, 2020)
Literature on driving research suggests a relationship between cognition and driving performance in older and younger drivers. There is little research on adults and driving, despite them being the largest age cohort behind the wheel. Among the cognitive domains, visuospatial abilities are expected to be highly predictive of driving skills and driving fitness. The relationship between specific spatial mental transformation skills (i.e., object and self-based ones) and driving performance has not yet been examined. The present study aimed to investigate the relationship between overall cognitive functioning, self and object-based spatial mental transformation skills, and driving performance in a sample of younger and older adult drivers. Participants were comprised of one hundred younger and 83 older adult Italian drivers. Participants completed a computerized driving test assessing traffic stress resilience, visual and motor reaction time, and the ability to obtain an overview of the traffic scenario (DT, vRT, mRT, and ATAV respectively in the Shufried®-Vienna Test System–DRIVESC). The Mental Rotation Test (MRT) and the Object Perspective Taking Test (OPT) were administered in order to assess object-based and self-based spatial mental transformation skills. The Montreal Cognitive Assessment Test (MoCA) was administered control for global cognitive functioning. The effects of education and gender were also controlled in the analysis. The results of the present study suggested that: (1) The effect of age, favoring younger participants, was found in DT, vRT, mRT, and ATAVT tests. (2) The effect of global cognitive functioning was found in DT and ATAV tests. (3) The effect of the spatial mental transformation tests was found in DT, vRT (MRT only), and ATAVT (OPT only) tests. Taken together, these results suggest the specific contribution of spatial mental transformation skills in the execution of complex behaviors connected to the fitness to drive. Prospectively, the results of the present study relating spatial mental transformation skills and driving processes may be a valuable source of knowledge for researchers dealing with the relationship between cognitive resources and navigation aids.